Efficacy of Stone Bunds for Resource Conservation in Hill Slopes of Eastern Ghats - Susamasudhishri; C.P.Arora; Anchal Dass (Journal of Soil and Water Conservation, 2022)
In tribal dominant Koraput district of Orissa practice of shifting cultivation is adopted on hill and hill slopes resulting into on site and off site environmental degradation problems. In order to prevent the situation permeable contour barriers of bushes, stones, bush buffer strips and stone bunding are the traditional conservation practices adopted by the farmers. Among these, stone bunding is found to be quite promising for erosion hazard management. Therefore evaluation of the process of stone bunding was conducted through field survey, personal visits and experimentation at two representative villages of Semiligida block and CSWCRTI, Research Center, Sunabeda, Koraput. It was found that on an average stone bund yielded 54, 59.6 and 59.3 per cent less runoff, soil loss and organic carbon loss respectively than control. Advantage in grain and straw yield due to stone bund was 60.8 and 58.2 per cent, respectively over control. Traditional practice of stone bunding is considered to be the immediate answer to the increasing erosion induced degradation problem in hilltops and hill slopes of hill slopes.